Calidad de control prenatal en gestantes del Hospital General Julius Doepfner - Pallo Buele, Arianna Marelys (2022)
The quality of care makes the difference between life and death of mothers and newborns, hence the importance of establishing a quality management of care that systematically directs, operates and controls the processes aimed at improving health care, involving the transformation of organizations. The main objective of this research is to analyze the quality of prenatal care received by pregnant women at Julius Doepfner General Hospital for the implementation of an action plan. This is a descriptive study with a quantitative, cross-sectional, cross-sectional approach, whose study population was 110 pregnant women attended at the Julius Doepfner General Hospital. The instrument used was the Donabedian Quality of Care Questionnaire, which contains 55 questions divided into three sections: structure, processes and results, as well as a sociodemographic data collection sheet. The data were tabulated and analyzed in Excel 2019 spreadsheet. The results are presented in tables of frequencies and percentages and show that 97% of the pregnant women perceive prenatal care in its structure dimension as good, in the process dimension 94% perceive good quality and in the results dimension 95% also perceive good quality. With these results, we conclude that the overall quality of prenatal care was perceived as of good quality, as well as in the structure, process and results dimensions